PETASAN, GEERTZ, DAN GREEN ISLAM - Chlaodhius Budhianto; Rinda Fauzian; Juju Saepudin (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
This paper intends to reexamine the theory of religious congruence from Clifford Geertz, which, whether we realize it or not, has become the basic assumption of Green Islam discourse. Textual studies and various activities of Green Islam have given birth to hope and optimism that Green Islam can form environmentally friendly behavior among the Ummah. This optimism in turn encourages scholars to examine Green Islam empirically, the firecracker explosion incident during Ramadan and Eid al-Fitr is a test case for this optimism. By using qualitative research methods and a living religion approach, the phenomenon of firecracker detonation was observed, and the perpetrators of the firecracker were interviewed. As a result, the firecracker explosion not only questions the optimism toward Green Islam but also presents theoretical problems regarding religious incompatibility. The orientation of firecracker explosions stems from assumptions and sheer enjoyment or can be described as an overflow or expression of joy in welcoming the festive season, disregarding the tranquillity of those in the vicinity. This is a basic problem in Green Islam studies to find new paths.